عناصر الاتساق والانسجام وأهميتها في تماسك الخطاب النبوي: حديث دواء المبطون - Muhammad Izuan Abd Gani; Asem Shahedeh Ali; Muhammad Adil Mufti Mohamad Samsuddin (Penerbit USIM, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Norms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.